Real-world costs and dynamics of surveillance in patients who underwent surgery for low-risk branch duct intraductal papillary mucinous neoplasms. Issue 1 (January 2023) - Tamburrino, Domenico; Cortesi, Paolo; Facchetti, Rita; de Pretis, Nicolò; Pérez-Cuadrado-Robles, Enrique; Uribarri-Gonzalez, Laura; Ateeb, Zeeshan; Belfiori, Giulio; Arcidiacono, Paolo Giorgio; Mantovani, Lorenzo Giovanni; Del Chiaro, Marco; Laukkarinen, Johanna; et al.
Abstract: Surveillance costs and appropriateness of surgery of "low-risk" BD-IPMNs are relevant issues. In this study we evaluated the rate of correct indication for pancreatectomy defined as high grade dysplasia (HGD) at histology in 961 patients who underwent surveillance for a median of 5.1 years. Undertreatment and overtreatment were defined as invasive cancer and low grade dysplasia (LGD) at histology, respectively. Of the 66 patients (6.9%) who were operated, only 16 (23.8%) had a HGD while 40 (59.7%) had a LGD and 10 (14.9%) an invasive cancer, without differences regarding timing of surgery. The mean surveillance cost was € 194.9 ± 107.6 per patient-year, with a median cost of € 277.1 ± 148.2 in the correct surgery group compared with € 222.7 ± 111.6 and € 197 ± 102.7 in the overtreatment and undertreatment groups. The surveillance mean cost from diagnosis to surgery was € 854.8. Rate of appropriate surgery in BD-IPMNs under surveillance is low.